Flucloxacillin-induced hypokalaemia: a case report. Issue 6 (2nd November 2018) - De Backer, Eva; Hannon, Heidi
Abstract: Objective and importance: Flucloxacillin is a narrow-spectrum beta-lactam antibiotic with activity against penicillinase producing staphylococci and streptococci . Severe hypokalaemia is an uncommon, but serious adverse effect in patients treated with penicillin derivates. Clinical presentation: We report a case of severe hypokalaemia in a patient treated with high dose intravenous flucloxacillin. Conclusion: This case report highlights the importance of monitoring electrolytes during treatment with high dose flucloxacillin. If severe hypokalaemia is noted during treatment, this should be considered in the differential diagnosis.